Determination and pharmacokinetic study of AZD‐3759 in rat plasma by ultra performance liquid chromatography with triple quadrupole mass spectrometer - Wu, Qingjun (Thorac Cancer, 2018)
BACKGROUND: AZD‐3759 is a new, potent, oral, active central nervous system‐penetrant EGFR inhibitor. Despite promising clinical activity among patients pretreated and never treated with EGFR‐tyrosine kinase inhibitors, no time saving pharmacokinetic study method has been reported in an animal model. METHODS: Protein was precipitated with acetonitrile and then used for sample pre‐processing. A CORTECS BEH C18 column was used to separate the analytes at 40°C. Acetonitrile and water (containing 0.1% formic acid) were chosen as the mobile phase at a flow rate of 0.4 mL/min. The analytes were quantified by multiple reaction monitoring mode with positive electrospray ionization. RESULTS: The target fragment ions were m/z 460.38→141 for AZD‐3759 and m/z 285.1→193.1 for internal standard diazepam. The calibration curve exhibited good linearity for AZD‐3759 at a range of 1–500 ng/mL. The intra‐run and inter‐run precision variations were both < 8.22%. The recovery rate of AZD‐3759 from plasma was > 76.4%. CONCLUSION: An accurate, simple ultra performance liquid chromatography with triple quadrupole mass spectrometer method was developed and validated to determine AZD‐3759 in rat plasma. Our validated method can be applied to the pharmacokinetic study of AZD‐3759 at an oral dosage of 10 mg/kg.